THE FEAR OF THE ‘OTHER’ IN THE AGE OF GLOBALIZATION. THE IMAGE OF ROMANIAN MIGRATION IN THE BRITISH PRESS - GABRIELA DUMBRAVĂ (Annals of the University of Petrosani: Economics)
The present study attempts to show that, in the age of declarative cosmopolitanism and globalization, the ancestral fear of ‘the Other’ keeps resurfacing under the form of nationalism and xenophobia, very often generated and fueled by the media themselves. In this sense, the paper presents a selection of news from major British printed media covering the event of the so-called ‘opening of the British borders’ for Bulgarian and Romanian workers in January 1, 2014, showing how they build into an aggressive antiforeigner discourse that proves beyond doubt that the ‘European ideal’ still remains pure theory.